3D Imaging for Safety and Security - Koschan, Andreas; Pollefeys, Marc.; Abidi, Mongi; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2007)
The past decades have seen significant improvements in 3D imaging where the related techniques and technologies have advanced to a mature state. These exciting developments have sparked increasing interest in industry and academia in the challenges and opportunities afforded by 3D sensing. As a consequence, the emerging area of safety and security related imaging incorporates these important new technologies beyond the limitations of 2D image processing. This is the first book that covers the current state of the art in 3D imaging for safety and security. Topics addressed in this book include 3D imaging related to biometrics, face recognition, surveillance, safety inspection and robotic planning for physical security analysis and public safety. The book presents thoroughly revised versions of lectures given by leading researchers during the 'Workshop on Advanced 3D Imaging for Safety and Security' in conjunction with the International Conference on Computer Vision and Pattern Recognition CVPR 2005 on June 25, 2005 in San Diego, USA.
Biometrics -- 3D Assisted Face Recognition: A Survey -- A Survey on 3D Modeling of Human Faces for Face Recognition -- Automatic 3D Face Registration Without Initialization -- A Genetic Algorithm Based Approach for 3D Face Recognition -- Story of Cinderella -- Human Ear Detection From 3D Side Face Range Images -- Safety and Security Applications -- Synthetic Aperture Focusing Using Dense Camera Arrays -- Dynamic Pushbroom Stereo Vision -- 3D Modeling of Indoor Environments -- 3D Site Modelling and Verification -- Under Vehicle Inspection with 3d Imaging.
Keywords: COMPUTER SCIENCE; COMPUTER VISION; COMPUTER GRAPHICS; OPTICAL PATTERN RECOGNITION; COMPUTER SCIENCE; COMPUTER IMAGING, VISION, PATTERN RECOGNITION AND GRAPHICS; IMAGE PROCESSING AND COMPUTER VISION; COMPUTER GRAPHICS; PATTERN RECOGNITION; MATH APPLICATIONS IN COMPUTER SCIENCE